The level of awareness towards money mules in Malaysia / Muhammad Saufi Zulqaram Rosli ... [et al.] - Rosli, Muhammad Saufi Zulqaram; Ahmad Shakir, Nur Irsya Alia; Ilyas, Ilya Yasnoriza; Bakar, Mohd Hilmi; Sultan Mohideen, Rosilawati; Md Zakaria, Mohd Hamzatul Akmar (Faculty of Communication & Media Studies, 2022)
Money laundering is seen as a worldwide problem, with cash originating from unlawful and fraudulent activities being used to finance it. Money mules are hired by criminal networks to operate in the money laundering chain, where they are positioned between the real criminal and the illegal payments, allowing the criminals to remain anonymous and untraceable to law enforcement. This research investigates the level of awareness towards money mules in Malaysia and the level of prevention towards money mules in Malaysia. Money mule is not a new phenomena, it has become more prominent especially among young people hit hard by economic problems as Malaysia is still in the process of restoring the financial economy after the damages had been caused by the global pandemic. The study is using a quantitative survey method through Google Form platform involving 391 respondents from various backgrounds. The result shows that the level of prevention towards money mules in Malaysia is very high (M=3.65), and the level of awareness towards money mules is also very high (M=3.53).